Double Jeopardy and G0vernment Appeals of Acquittals (1989)
As part of a continuing series of papers on impediments to the search for truth in criminal investigation and adjudication, the Office of Legal Policy has carried out a review of the law governing double jeopardy prohibitions on federal government appeals of criminal acquittals. These prohibitions undermine the search for truth in criminal adjudication by allowing some wrongly acquitted, culpable individuals to go unpunished. The results of our review are set out in this Report